2007
DOI: 10.1002/art.23145
|View full text |Cite
|
Sign up to set email alerts
|

Differentially regulated expression of growth differentiation factor 5 and bone morphogenetic protein 7 in articular cartilage and synovium in murine chronic arthritis: Potential importance for cartilage breakdown and synovial hypertrophy

Abstract: In this murine model of TNFalpha-mediated arthritis, the expression of GDF-5 and BMP-7 is regulated differentially in articular cartilage and synovium. In articular cartilage, the down-regulation of GDF-5 and BMP-7, which function to maintain matrix integrity, could potentially compromise tissue repair, whereas in synovium, the increased expression of GDF-5 and BMP-7 might contribute to synovial hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
(55 reference statements)
1
18
0
Order By: Relevance
“…These data reveal that the upstream and downstream regions contain enhancers active during both early joint formation, and in joint homeostasis during post-natal life. Such expression is expected, since endogenous Gdf5 expression has also been detected in the adult articular cartilage and joint tissues of both mice and humans [29, 34, 35]. …”
Section: Resultsmentioning
confidence: 99%
“…These data reveal that the upstream and downstream regions contain enhancers active during both early joint formation, and in joint homeostasis during post-natal life. Such expression is expected, since endogenous Gdf5 expression has also been detected in the adult articular cartilage and joint tissues of both mice and humans [29, 34, 35]. …”
Section: Resultsmentioning
confidence: 99%
“…Although the presence of BMP-7 has also been observed in the synovium in both the ZIA and BMP-7-treated groups, the level of BMP-7 in synovium is not significantly different between the two groups. Interestingly, Bobacz et al (2008) have demonstrated that BMP-7 is overexpressed in the arthritic synovium of hTNFtg mice. In Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Many more studies have focused on the roles FLS play in pathophysiology of inflammatory disease exploring their contribution to leukocyte activation and driving the inflammatory process [54-56]. Importantly, work focusing on murine FLS culture in inflammatory models have provided greater insights into synoviocyte survival, migration, proliferation and contribution towards joint destruction that occur in human FLS-mediated disease [57-60]. …”
Section: Discussionmentioning
confidence: 99%